Poor whites of the antebellum South : tenants and laborers in central North Carolina and northeast Mississippi - Bolton, Charles C. (Duke University Press, 1994)
In Poor Whites of the Antebellum South, Charles C. Bolton gives a distinct voice to one of the most elusive groups in the society of the Old South. Bolton's detailed examination reveals much about the lives of these landless white tenants and laborers and their relationship to yeoman farmers, black slaves, free blacks and elite whites. Providing a provocative analysis of the failure of the Jeffersonian "yeoman ideal" of democracy in white-majority areas, this book also shows how poor whites represented a more significant presence on the political, economic, and social landscape than previously had been thought. Looking at two specific regions--the "settled" central piedmont of North Carolina and the "frontier" of northeast Mississippi--Bolton describes how poor whites played an important, though circumscribed, role in the local economy. Dependent on temporary employment, they represented a troubling presence in a society based on the principles of white independence and black slavery. Although perceived by southern leaders as a threat, poor whites, Bolton argues, did not form a political alliance with either free or enslaved blacks because of numerous factors including white racism, kinship ties, religion, education, and mobility. A concluding discussion of the crisis of 1860-61 examines the rejection of secession by significant numbers of poor whites, as well as the implications for their future as the Old South turned toward the new. Poor Whites of the Antebellum South sheds light on a group often neglected in southern history. It is an important contribution that will be of interest to all students and historians of the American South